GATA2 hypomorphism induces chronic myelomonocytic leukemia in mice - Harada, Nobuhiko (Cancer Sci, 2019)
The transcription factor GATA2 regulates normal hematopoiesis, particularly in‐ stem cell maintenance and myeloid differentiation. Various heteroallelic GATA2 gene mutations are associated with a variety of hematological neoplasms, including myelodysplastic syndromes and leukemias. Here, we report that impaired GATA2 expression induces myelodysplastic and myeloproliferative neoplasm development in elderly animals, and this neoplasm resembles chronic myelomonocytic leukemia in humans. GATA2 hypomorphic mutant (G2 (f) (GN) (/) (fGN)) mice that were generated by the germline insertion of a neocassette into the Gata2 gene locus avoided the early embryonic lethality observed in Gata2‐null mice. However, adult G2 (f) (GN) (/) (fGN) mice suffered from exacerbated leukocytosis concomitant with progressive anemia and thrombocytopenia and eventually developed massive granulomonocytosis accompanied by trilineage dysplasia. The reconstitution activity of G2 (f) (GN) (/) (fGN) mouse stem cells was impaired. Furthermore, G2 (f) (GN) (/) (fGN) progenitors showed myeloid lineage‐biased proliferation and differentiation. Myeloid progenitor accumulation started at a younger age in G2 (f) (GN) (/) (fGN) mice and appeared to worsen with age. G2 (f) (GN) (/) (fGN) mice showed increased expression of transcripts encoding cytokine receptors, such as macrophage colony‐stimulating factor receptor and interleukin‐6 receptor, in granulocyte‐monocyte progenitors. This increased expression could be correlated with the hypersensitive granulomonocytic proliferation reaction when the mice were exposed to lipopolysaccharide. Taken together, these observations indicate that GATA2 hypomorphism leads to a hyperreactive defense response to infections, and this reaction is attributed to a unique intrinsic cell defect in the regulation of myeloid expansion that increases the risk of hematological neoplasm transformation.